1981
DOI: 10.1002/jpln.19811440403
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of iron‐stress reactions in sunflower by bicarbonate

Abstract: In pot culture experiments using a calcareous soil the growth rate of sunflowers was depressed by latent iron deficiency. Iron‐stress reactions, reflected by enhanced uptake rate of Fe‐59 after short‐term supply of 59FeEDDHA were observed under these conditions. These reactions, however, were delayed and much less distinct than those observed under latent iron deficiency in water culture experiments. Addition of MgCO3 to this soil increased the iron deficiency of the plants and caused chlorosis, but prevented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…It has been demonstrated previously by many authors that bicarbonate in the rooting medium decreases Fe accumulation in the shoots (Venkat Raju and Downloaded by [Northeastern University] at 03:46 08 January 2015 Marschner, 1981;Inskeep and Bloom, 1986). Our results fully confirm these findings (Table 1 ).…”
Section: Discussionsupporting
confidence: 96%
“…It has been demonstrated previously by many authors that bicarbonate in the rooting medium decreases Fe accumulation in the shoots (Venkat Raju and Downloaded by [Northeastern University] at 03:46 08 January 2015 Marschner, 1981;Inskeep and Bloom, 1986). Our results fully confirm these findings (Table 1 ).…”
Section: Discussionsupporting
confidence: 96%
“…In view of these recent observations on a direct role of bicarbonate, further research is needed to characterize regulation of Fe-stressresponse. Much research has indicated an important role for bicarbonate in lime-induced chlorosis of dicotyledonous plants (Wadleigh and Brown, 1952;Porter and Thorne, 1955;Rutland and Bukovac, 1971;Boxma, 1972;Venkatraju and Marschner, 1981). Many aspects of Fe-stress-response were Illustrated in these screening experiments.…”
Section: Resultsmentioning
confidence: 98%
“…Elevated bicarbonate concentrations and high pH have been identified as the main soil conditions explaining the incidence of Fe chlorosis (Boxma 1972;Mengel et al 1984;Shi et al 1993). Under such conditions, the solubility of Fe(hydr)oxides is low (Lindsay 1979) and Fe uptake mechanisms become impaired (Marschner 1995;Venkatraju and Marschner 1981) or Fe becomes inactivated inside the leaf's apoplast (Mengel 1994).…”
Section: Introductionmentioning
confidence: 98%